Vibrio aestuarianus subsp. cardii subsp. nov., pathogenic to the edible cockles Cerastoderma edule in France, and establishment of Vibrio aestuarianus subsp. aestuarianus subsp. nov. and Vibrio aestuarianus subsp. francensis subsp. nov. - Garcia, Celine; Mesnil, Aurelie; Tourbiez, Delphine; Moussa Pouly, Mirna; Dubreuil, Christine; Gonçalves De Sa, Amélie; Chollet, Bruno; Godfrin, Yoann; Dégremont, Lionel; Serpin, Delphine; Travers, Marie-agnes (International Journal of Systematic and Evolutionary Microbiology, 2021)
Cockle mortality events have been reported in northern France since 2012. In the present study, we describe and investigate the implication of a potential bacterial causative agent in cockle mortality. Bacteria isolated from five different cockle mortality events were characterized and studied. Using phenotypic analysis combined with DNA–DNA hybridization (DDH) and whole genome sequencing, the isolates were shown to belong to Vibrio aestuarianus , a species regularly detected in France during oyster mortality events. Comparison of the strains from cockles with strains from French oysters and the type strain showed that the strains from cockles were genetically different to those from oysters and also different to the V. aestuarianus type strain. Moreover, the cockle and oyster strains were classified into two different, but close, groups both separated from the type strain by: (1) analyses of the ldh gene sequences; (2) DDH assays between 12/122 3T3T (LMG 31436T=DSM 109723T), a representative cockle strain, 02/041T (CIP 109791T=LMG 24517T) representative oyster strain and V. aestuarianus type strain LMG 7909T; (3) average nucleotide identity values calculated on the genomes; and (4) phenotypic traits. Finally, results of MALDI-TOF analyses also revealed specific peaks discriminating the three representative strains. The toxicity of representative strains of these cockle isolates was demonstrated by experimental infection of hatchery-produced cockles. The data therefore allow us to propose two novel subspecies of Vibrio aestuarianus : Vibrio aestuarianus subsp. cardii subsp. nov. for the cockle strains and Vibrio aestuarianus subsp. francensis subsp. nov. for the Pacific oyster strains, in addition to an emended description of the species Vibrio aestuarianus .